1998
DOI: 10.1161/01.cir.97.10.971
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Factor in Mast Cells and Increased Mast Cell Density in Idiopathic and Ischemic Cardiomyopathy

Abstract: Background-We compared cardiac mast cell (HHMC) density and the immunological and nonimmunological release of mediators from mast cells isolated from heart tissue of patients with idiopathic dilated (DCM) (nϭ24) and ischemic cardiomyopathy (ICM) (nϭ10) undergoing heart transplantation and from control subjects (nϭ10) without cardiovascular disease. Methods and Results-HHMC density in DCM (18.4Ϯ1.6 cells/mm 2 ) and ICM (18.4Ϯ1.5 cells/mm 2 ) was higher than that in control hearts (5.3Ϯ0.7 cells/mm 2 ; PϽ.01). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
206
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(217 citation statements)
references
References 53 publications
9
206
0
2
Order By: Relevance
“…Increased histamine concentration in cardiac tissue also corresponds to increased mast cell density [16]. In clinical situations, the presence of mast cells around and within the coronary blood vessels has been implicated in the pathophysiology of coronary artery disease [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased histamine concentration in cardiac tissue also corresponds to increased mast cell density [16]. In clinical situations, the presence of mast cells around and within the coronary blood vessels has been implicated in the pathophysiology of coronary artery disease [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…These cells have also been demonstrated to be associated with various cardiovascular inflammatory conditions, including hypertensive cardiac hypertrophy [14], ischemia-reperfusion injury [15], ischemic cardiomyopathy [16] and cardiac allograft rejection [17]. In 1968, Fernex [18] [DOI 10.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed with human hearts obtained from recipients of transplants have shown clearly that cardiac tissue from patients with ischaemic or dilated cardiomyopathies contains a significantly larger number of mast cells compared to hearts from normal individuals who have died accidentally [24]. Consequently, the cardiac tissue from patients with heart diseases contains and releases larger quantities of mast cell-derived mediators upon immunological and non-immunological activation [24].…”
Section: The Heart As a Source Of Mediators Of Anaphylaxismentioning
confidence: 99%
“…Consequently, the cardiac tissue from patients with heart diseases contains and releases larger quantities of mast cell-derived mediators upon immunological and non-immunological activation [24]. These observations may contribute to explaining why cardiac manifestations of anaphylaxis are more severe in patients with ischaemic or degenerative heart diseases.…”
Section: The Heart As a Source Of Mediators Of Anaphylaxismentioning
confidence: 99%
“…Thrombin activation of the vascular endothelium occurring in response to vascular injury or wounding can be beneficial in the repair process, but has the potential to mediate a prolonged inflammatory response and proliferative cellular events in the blood vessel wall, such as those that occur in atherosclerosis and restenosis [13]. Similarly, increased numbers of degranulated mast cells have been found in the adventitia of infarct-related coronary arteries [14] and the mediators released from these granules, including tryptase, are mitogens and co-mitogens for human fibroblasts, stimulating collagen synthesis [15]. Though these studies demonstrate the presence of either thrombin or tryptase associated with atherosclerosis, a defined role has yet to be established for these proteases.…”
mentioning
confidence: 99%